(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In the ever-evolving landscape of modern business, the term "Digital Business Ecosystems" (DBEs) has emerged as a cornerstone concept driving innovation, collaboration, and growth. Yet, despite its prevalence, the understanding of DBEs remains varied and nuanced. This article embarks on a journey to define and demystify DBEs, unraveling their intricacies, components, and significance in today’s digital age.